2016
DOI: 10.1095/biolreprod.115.137240
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Ovaries: Measurement and Physiology1

Abstract: Traditionally, research in the field of trace element biology and human and animal health has largely depended on epidemiological methods to demonstrate involvement in biological processes. These studies were typically followed by trace element supplementation trials or attempts at identification of the biochemical pathways involved. With the discovery of biological molecules that contain the trace elements, such as matrix metalloproteinases containing zinc (Zn), cytochrome P450 enzymes containing iron (Fe), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 140 publications
1
25
0
1
Order By: Relevance
“…The significant decreased magnesium concentration in the current study may participate in infertility because magnesium deficiency associates with variable complications of female reproductive system. Our results revealed that serum zinc concentration was significantly reduced in infertile group in comparison with the fertile group, this showed that zinc deficiency can play a negative significant role in female infertility and this was related to other previous studies demonstrated the same like the founding of Ceko et al (2016), Zinc deficiency causes impaired synthesis and secretion of LH and FSH which leads to disruption of the pituitary-ovarian axis function and estrous cycle (Bedwal and Bahuguna, 1994).the data showed a significant elevation in the level of serum IL-1β between infertile and fertile groups. This result was not corresponded with the study of Kalu et al (2007) on infertile women, who were found that serum level of IL-1β was not significantly different in the patients and controls.…”
Section: Discussionsupporting
confidence: 87%
“…The significant decreased magnesium concentration in the current study may participate in infertility because magnesium deficiency associates with variable complications of female reproductive system. Our results revealed that serum zinc concentration was significantly reduced in infertile group in comparison with the fertile group, this showed that zinc deficiency can play a negative significant role in female infertility and this was related to other previous studies demonstrated the same like the founding of Ceko et al (2016), Zinc deficiency causes impaired synthesis and secretion of LH and FSH which leads to disruption of the pituitary-ovarian axis function and estrous cycle (Bedwal and Bahuguna, 1994).the data showed a significant elevation in the level of serum IL-1β between infertile and fertile groups. This result was not corresponded with the study of Kalu et al (2007) on infertile women, who were found that serum level of IL-1β was not significantly different in the patients and controls.…”
Section: Discussionsupporting
confidence: 87%
“…The most commonly used measures of selenium status are plasma and serum selenium concentrations, which reflect recent dietary selenium intake [30]. Functional measures of selenium status include the glutathione peroxidases and selenoprotein P which play important roles in antioxidant defence, formation of thyroid hormones, and DNA synthesis, all of which impact fertility and reproduction [8,10]. While there have been studies demonstrating that low selenium status during pregnancy is associated with pregnancy complications [31], roles of selenium in periconceptual events such as oocyte development, fertilisation, and implantation, have not been addressed to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been studies demonstrating that low selenium status during pregnancy is associated with pregnancy complications [31], roles of selenium in periconceptual events such as oocyte development, fertilisation, and implantation, have not been addressed to a large extent. However, there are reports of its potential importance in follicle growth and maturation [10]. The importance of selenium in male fertility has been extensively studied in humans and animals, particularly in regard to the biosynthesis of testosterone but also potentially in sperm motility [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium is necessary for human reproduction [100]. We have recently shown that in 1060 Australian pregnant women, those who had lower selenium concentrations (<0.95 micromol per litre) took a longer time to conceive (1.19 (1.01-1.40)), an equivalent of around 0.6 months, and they were at greater risk of infertility (1.46 (1.06-2.03)) [101].…”
Section: Selenium and Pregnancy Complicationsmentioning
confidence: 99%